Synthesis of E-Isomer of α-Hydrazone Phosphonates via Nucleophilic Addition of Trialkyl Phosphite to Nitrile Imines (NIs) and DFT Calculations - Sinem Altınışık; Sıdıka Polat Çakır (Journal of Advanced Research in Natural and Applied Sciences)
Nitrile imines (NIs) belong to the nitrilium betaine family of 1,3-dipoles. Due to their high reactivity, NI compounds cannot be isolated and must be generated in situ before undergoing the desired transformation. NI derivatives were prepared by the utilization of N-phenyl hydrazine chloride precursors in the presence of a base. The title compounds α-hydrazone phosphonates have the potential to be biologically active and may serve as a precursor compound for other biologically active substances like amino phosphonic acids. Shortly, they are highly significant compounds in medicinal and synthetic chemistry. The derivatives of α-hydrazone phosphonate are synthesized by the nucleophilic addition of trialkyl phosphite to in situ generated NI derivatives and obtained in 44-95% isolated chemical yields. It is worth noting that only the E-isomer of the α-hydrazone phosphonates was obtained. Structural analyses of the α-hydrazone phosphonates were conducted by using proton and carbon NMR analysis along with FTIR. The researchers also performed DFT calculations including structural parameters (bond length, bond angle, and dihedral angle), HOMO and LUMO energy levels, and the zero-point vibrational energy (ZPE) for both E and Z geometric isomers of unsubstituted phenyl α-hydrazone phosphonate.